The letters of Hildegard of Bingen. Vol. 2 - Hildegard, Saint, 1098-1179.; Baird, Joseph L.; Ehrman, Radd K. (New York ; Oxford : Oxford University Press, 1998)
Annotation This is the second volume in what will be a translation with full scholarly apparatus of the entire correspondence of St. Hildegard of Bingen (1098-1179). The translation follows Van Acker's definitive new edition of the Latin text, which is being published serially in Belgium by Brepols. Asin that edition, the letters are organized according to the rank of the addressees. The first volume included ninety letters to and from the highest ranking prelates in Hildegard's world: popes, archbishops, and bishops. Volume II comprises letters 91-217, in which Hildegard addresses lower-rankingspiritual leaders (abbots and abbesses, for the most part) offering advice and consolation, and is particularly noteworthy for the correspondence with Guilbert of Gembloux, who provides a wealth of information about the saint and her spiritual gift.
MetzNeuenburg; Neuss (St. Quirin); Otterberg; Park; Pfalzel(?); Regensburg (St. Emmeram); Regensburg (Niedermünster); Regensburg (Obermünster); Reutlingen; Reutlingen(?); Rome (St. Anastasius); Rothenkirchen(?); Mount St. Rupert; St. Georgen; St. Nabor; St. Thomas an der Kyll(?); St. Walburga; Salem; Schönau; Selbod; Siegburg (St. Michael); Springiersbach; Tholey; Trier (St. Eucharius); Endnotes; Supplemental Bibliography; Scripture Index; General Index
Translated from the Latin.
Includes index.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Hildegard, -- Saint, -- 1098-1179 -- Correspondence; Hildegard, -- Saint, -- 1098-1179; Christian saints -- Germany -- Correspondence; Saints chrétiens -- Allemagne -- Correspondance; RELIGION -- Christianity -- Catholic; Christian saints; Germany; Personal correspondence; Brieven (vorm)